Core‐Shell Nanostructures: Dynamic Control of Orthogonal Upconversion in Migratory Core–Shell Nanostructure toward Information Security (Adv. Funct. Mater. 14/2021). (1st April 2021) - Huang, Jinshu; Yan, Long; Liu, Songbin; Song, Nan; Zhang, Qinyuan; Zhou, Bo
Abstract : In article number 2009796, Bo Zhou and co‐workers propose a novel simple migratory core–shell conceptual model for orthogonal upconversion. The red‐to‐green switchable output is easily achieved by dynamic control of the upconversion by altering the excitation wavelengths (e.g., 980/1530 nm) or using the non‐steady state excitation, showing great promise in the multi‐level information security.